Differential protective effects of Family Income-to-Poverty-Ratio on electronic cigarette, depression, and obesity of Black and White Americans - Shervin Assari (AIMS Public Health)
BackgroundThe Family Income-to-Poverty-Ratio (FIPR) is a recognized indicator of socioeconomic status, and influences a wide range of health and behavioral outcomes. Yet, marginalized and racialized groups, particularly Black individuals, may not reap comparable health benefits from their socioeconomic advancements as their non-Hispanic, White counterparts. This discrepancy is indicative of a phenomenon known as the minorities' diminished returns.AimsThis study investigates the differential impact of the FIPR on depression, obesity, tobacco use, and e-cigarette use between Black and White adults.MethodsUsing data from the 2022 National Health Interview Survey (NHIS), which included 21,354 non-Hispanic adults from both White and Black racial groups, this research employed structural equation modeling to assess the relationship between the FIPR and health outcomes, including depression, obesity, and e-cigarette use.ResultsThe analysis identified significant interactions between FIPR and race across all the examined outcomes. Contrary to expectations, the findings suggest that the protective effects of higher income levels on health and healthy behaviors are less pronounced for Black individuals compared to White individuals.ConclusionThe study underscores the substantial societal and environmental barriers that hinder Black families and individuals from converting their FIPR and socioeconomic resources into concrete health benefits, such as an enhanced mental and physical well-being. To redress these racial health disparities, targeted interventions are crucial, particularly those that focus on bridging the employment and marriage rate gaps caused by educational disparities among Black communities. A comprehensive approach that extends beyond simple access to education is imperative to eliminate the societal obstacles that limit the socioeconomic benefits for Black populations.